Cold homes, fuel poverty and energy efficiency improvements: A longitudinal focus group approach. Issue 7 (August 2017) - Grey, Charlotte N. B.; Schmieder-Gaite, Tina; Jiang, Shiyu; Nascimento, Christina; Poortinga, Wouter
Cold homes and fuel poverty have been identified as factors in health and social inequalities that could be alleviated through energy efficiency interventions. Research on fuel poverty and the health impacts of affordable warmth initiatives have to date primarily been conducted using quantitative and statistical methods, limiting the way how fuel poverty is understood. This study took a longitudinal focus group approach that allowed exploration of lived experiences of fuel poverty before and after an energy efficiency intervention. Focus group discussions were held with residents from three low-income communities before (n = 28) and after (n = 22) they received energy efficiency measures funded through a government-led scheme. The results show that improving the energy efficiency of homes at risk of fuel poverty has a profound impact on wellbeing and quality of life, financial stress, thermal comfort, social interactions and indoor space use. However, the process of receiving the intervention was experienced by some as stressful. There is a need for better community engagement and communication to improve the benefits delivered by fuel poverty programmes, as well as further qualitative exploration to better understand the wider impacts of fuel poverty and policy-led intervention schemes.